THE AFFECT OF THE SIZE OF COMMISSIONERS BOARD AND THE SIZE OF THE COMPANY REGARDING THE ENVIRONMENTAL DISCLOSURE - Desy Anggrarini; Eindye Taufiq (STIE Binaniaga, 2016)
This research aims to examine and to prove empirically the size of Commissioners Board and the size of the Company regarding the Environmental Disclosure. It has been identifying the manufacturing companies registered in the Indonesia Stock Exchange Market as the samples. Sampling technique has applied purposive sampling method. Sampling is 92 from 149 manufacturing companies registered in the Indonesia Stock Exchange Market in 2014. This research has applied secondary data obtained from website www.idx.co.id. Hypothesis analysis of this research has applied the analysis of Multiple Linier Regression using SPSS 21 with a significant level of 5%. The result of this research has indicated that the size of a commissioners board has not affected the environmental disclosure, but the size of a company has unsignificantly affected the environmental disclosure.Keywords : The size of a commissioners board, the size of a company, and the environmental disclosure.